Effectiveness of Vaccines Booster Against Infection, Severe Disease and Death Related to COVID-19 : A Systematic Review and Meta-Analysis - Khalisha, Mujahidah; Putri, Melvanda Gisela; Ramadhani, Zulfa Nurfitri; Siahaan, Paulus Parholong; Razan, Rafi Alfian; Antari, Ratna Devi; Hanifah, Adiba Hasna; Utomo, Budi; Fauziyah, Shifa; Muthu, Pandaram (Institute of Topical Disease Universitas Airlangga, 2024)
COVID-19 is an infectious disease as a result of a kind of corona virus. COVID-19 is now a pandemic affecting many countries. This study aims to know the effectiveness of booster vaccines to reduce the severity of illness, confirm infection, hospitalization, death in humans infected with COVID-19. For Specific purpose, to analyze the severity of COVID-19 disease in humans by booster and without booster. The design of this study was a systematic review and meta-analysis based on observational studies, published in databases such as Pubmed, Embase, MedRxiv, Nature and Scopus. In the search for articles, the limitations of 2021 to 2022 are used. This research was analyzed quantitatively through the Review Manager 5.4.1 program. Study was taken from 13 journals that met the criteria for a meta-analysis. With the population aged over 18 years, and using the type of vaccine BNT162b2 or mRNA. The population of this study came from Israel, Italy, England, Qatar, Brazil, Turkey, Puerto-Rico, Northern Bangkok, Vicinities and Thailand. Significant results were obtained for each outcome. The OR values of BNT162b2 booster vaccine against confirmed infection OR 0.16 (95% CI 0.06 – 0.45), against symptomatic disease 0.22 (95% CI 0.11 – 0.44), against asymptomatic disease OR 0.72 (95% CI 0.69 – 0.74), against hospitalization OR 0.12 (95% CI 0.06 – 0.22), against severe disease OR 0.15 (95% CI 0.07 – 0.33), and against death OR 0.10 (95% CI 0.04 – 0.31). Administration booster vaccines is effective in reducing infection rates, disease severity, and deaths from COVID-19.